Exporting pollution: where do multinational firms emit CO2?. (10th February 2021) - Ben-David, Itzhak; Jang, Yeejin; Kleimeier, Stefanie; Viehs, Michael
SUMMARY: Despite widespread awareness of the detrimental impact of CO2 pollution on the world climate, countries vary widely in how they design and enforce environmental laws. Using novel microdata about multinational firms' CO2 emissions across countries, we document that firms headquartered in countries with strict environmental policies perform their polluting activities abroad in countries with relatively weaker policies. These effects are largely driven by tightened environmental policies in home countries that incentivize firms to pollute abroad rather than lenient foreign policies that attract those firms. Although firms headquartered in countries with strict domestic environmental policies are more likely to export pollution to foreign countries, they nevertheless emit somewhat less overall CO2 globally.